Sensibilidade do barorreflexo e respostas cardiorrespiratórias após a ativação e desativação do barorreflexo em ratos depletados de sódio - Borsari, Karine Cristina (2015)
Cardiorespiratory responses to peripheral baroreceptor activation are affected by sodium balance or anesthesia. In the present study, we investigated the baroreflex sensitivity and cardiorespiratory responses: to baroreceptor activation and deactivation with intravenous (iv) infusions of phenylephrine (phenyl) and sodium nitroprusside (NP) with or without angiotensinergic type 1 receptor (AT1) blocking; to baroreceptor activation with iv infusions of angiotensin II (ANG II), and cardiorespiratory responses: to cardiopulmonary receptor activation with iv infusions of fenilbiguanide: to chemoreceptor activation with iv infusions of sodium nitroprusside (KCN) in normovolemic, sodium depleted, and sodium repleted unanesthetized rats. Male Holtzman rats (280-320 g, n = 8 - 19) with a polyethylene tubing inserted into abdominal aorta through femoral artery to record mean arterial pressure (MAP) and heart rate (HR) and femoral vein to perform iv administration drugs were used. Respiratory frequency (fR), tidal volume (VT) and ventilation (VE) were recorded by whole-body plethysmography. Sodium depletion did not modify baseline MAP (102 ± 2, vs. normovolemic: 107 ± 2 mmHg), HR (382 ± 9, vs. normovolemic: 385 ± 7 bpm) or VE (468 ± 27, vs. normovolemic: 447 ± 26 ml/min/kg). Iv infusion of phenyl (5 μg/kg/ml, 0.011ml/s) in normovolemic, sodium depleted and repleted rats produced similar pressor (Δ +58  2, +59  2 and +60  3 mmHg, respectively) and bradycardic (Δ -97  10, -120  11 and -110  9 bpm, respectively) responses, however, sodium depleted rats showed an increased in VE (Δ +152  40, vs. normovolemic: +53 ± 26 ml/min/kg, p<0.05). After sodium repletion the VE returned to approximate value of normovolemic rats (Δ +125  50 ml/min/kg). In the other group of animal was made AT1 receptor blocking with iv bolus injections of losartan and was observed an attenuation of VE that was increased in sodium depleted rats (Δ +77 ± 33 ml/min/kg). 9 The bradicardic component gain also was increased in depleted rats (-1.9 ± 0.1, vs. normovolemic: -1.3 ± 0.1 bpm/mmHg, p<0.05) and returned to baselines values in sodium repleted rats (-1.5 ± 0.1 bpm/mmHg). Iv Infusion of NP (30 μg/kg/ml, 0.011ml/s) in normovolemic, sodium depleted and repleted rats produced similar hypotensive, tachycardic responses, similar VE and the tachycardic component gain. The iv infusion of fenilbiguanide (50 μg/kg/ml) induced similar hypotensive and bradicardic responses in normovolemic and sodium depleted rats, however increased VE in sodium depleted rats (Δ +281 ± 34, vs. normovolemic: +150 ± 50 ml/min/kg, p <0.05). Iv infusion of potassium cyanide (KCN, 40 μg/0.1ml per rat) did not change cardiorespiratory responses. Thus, the results suggest that sodium depletion with furosemide plus sodium-deficient diet increased bradicardic component of baroreflex and the neurondocrine changes produced by sodium depletion (like increased angiotensin II) may facilitate respiratory responses to baroreceptor activation with phenyl iv.